1998
DOI: 10.1038/sj.bmt.1701068
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mortality following bone marrow transplantation for breast cancer with the addition of peripheral blood progenitor cells is due to a marked reduction in veno-occlusive disease of the liver

Abstract: Summary:results and to the marked reduction in toxic mortality associated with this procedure. Over the past decade, there have also been significant Clinical trials involving breast cancer in the Duke University Bone Marrow Transplant Program were evaluimprovements in supportive care for patients undergoing high-dose chemotherapy, including better transfusion supated to assess the association between type of hematopoietic support and treatment-related morbidity/ port and treatment of infections. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
2
9
0
3
Order By: Relevance
“…This was attributed to the selection of a noncarmustine-based transplant protocol, the use of peripheral blood stem-cell support, and better supportive care. This low treatment-related mortality was in accordance with other studies (8,10,11,13,18,21,24).…”
Section: Discussionsupporting
confidence: 80%
“…This was attributed to the selection of a noncarmustine-based transplant protocol, the use of peripheral blood stem-cell support, and better supportive care. This low treatment-related mortality was in accordance with other studies (8,10,11,13,18,21,24).…”
Section: Discussionsupporting
confidence: 80%
“…[19][20][21][22][23][24] Only in the autologous setting, one study has reported a lower incidence of VOD after transplantation with both bone marrow and peripheral blood stem cells than after transplantation with bone marrow stem cells alone. 25 On the other hand, although the use of MTX for GVHD prophylaxis has emerged as a potential risk factor for VOD in one series, 26 several large studies have failed to show any association. [4][5][6] However, all these variables were associated with the risk of VOD by univariate analysis in our series and they had a heterogeneous distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[144][145][146] Glutamine supplementation, use of peripheral blood progenitor cells as opposed to those derived from the bone marrow, and T-cell depletion as prophylaxis against graft-versushost disease have been reported as having reduced incidence of SOS. 147,148 In the pediatric population undergoing HSCT, a prophylactic regime of enoxaparin or ursodeoxycholic acid and vitamin E has been of potential value. 149 Lastly, aggressive fluid management and control of fluid balance during the course of HSCT are essential.…”
Section: Preventionmentioning
confidence: 99%